(untitled) (Socio-economic relations in the digital society, 2019)
In thi this paper the impact of modern socio-economic processes on the development of higher education in Ukraine is briefl y presented. Positive and negative consequences of this process are investigated as well as the main tasks of development of higher education. Th e variant of competitive strategy methods of higher institutions’ developing and an algorithm for its implementation are offered. The procedures for individual indicators’ calculating of the educational services’ eff ectiveness are formalized. Substantiated variants of application of some of marketing tools for developing of competitive strategy (matrix of I. Ansoff , of M. Porter). The ways for the scientific results’ implementation in the creation of a competitive educational systems are performed.